The Power of Public Service Motivation as Mediator: Strengthening Servant Leadership and Organizational Culture to Achieve Employee Performance? - Domas Mifta Mudita; Putri Mega Desiana (Smart Society, 2025)
Public service motivation is fundamental to the essence of public service. It is supported by the role of servant leadership and organizational culture which are promoted by Indonesian government to enhance employee performance. This study aims to determine the influence of public service motivation mediation on employee performance through servant leadership and organizational culture in Government Educational Organizations (GEO). Data collected through online questionnaire distributed cross-sectionally, and 272 employees of GEO located in Jakarta-Bogor-Depok-Tangerang-Bekasi participated. The relationship between variables was analyzed through structural equation modeling (SEM) using SmartPLS 3. This study finds that public service motivation should be developed in order to improve employee performance through the implementation of organizational culture and servant leadership. Combining servant leadership, organizational culture, and public service motivation allows employees to follow the leader in a supportive environment and perform at their highest level, which helps the organization succeed